The Value of Connections: Evidence from the Italian-American Mafia - Giovanni Mastrobuoni (Institute for the Study of Labor (IZA), 2014)
Using declassified Federal Bureau of Narcotics records on 800 US Mafia members active in the 1950s and 1960s, and on their connections within the organized crime network, I estimate network effects on gangsters' economic status. Lacking information on criminal proceeds, I measure economic status exploiting detailed information about their place of residence. Housing values are reconstructed using current deflated transactions recorded on Zillow.com. I deal with the potential reverse causality between the economic status and the gangster's position in the network exploiting exogenous exposure to potential pre-immigration connections. In the absence of pre-immigration data I use the informational content of surnames, called isonomy, to measure the place of origin. The instrument is valid as long as conditional on the characteristics of the gangsters (including the region of birth and a rich set of controls about the gangsters' legal and illegal activities) such exposure influences the gangsters' importance in- side the network (called centrality) but not the preference for specific housing needs. A standard deviation increase in closeness centrality increases economic status by between one forth (OLS) and one standard deviation (2SLS).
Keywords: A14; C21; D23; D85; K42; Z13; 330; mafia; networks; centrality; housing prices; value of connections; crime; surnames; isonomy